R & D-Based Models of Economic Growth - Jones, Charles I. (Journal of Political Economy, 1995)
This paper argues that the "scale effects" prediction of many recent R & D-based models of growth is inconsistent with the time-series evidence from industrialized economies. A modified version of the Romer model that is consistent with this evidence is proposed, but the extended model alters a key implication usually found in endogenous growth theory. Although growth in the extended model is generated endogenously through R & D, the long-run growth rate depends only on parameters that are usually taken to be exogenous, including the rate of population growth.